Joining method
Patent Information
- Application Number
- JP2021142627
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-01
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2041-09-01
AI Technical Summary
【0010】 本開示によれば、インサート材が液相を形成するまでは不活性ガスを供給し、その後は不活性ガスの供給量を減少させることによって、不活性ガスの使用量を可能な限り低減しつつ、実用上充分な接合強度が得られる、金属材料の接合方法を提供することができる。
Smart Images

Figure 0007637944000001 
Figure 0007637944000002 
Figure 0007637944000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a joining method, and more particularly to a joining method using an insert material. [Background technology]
[0002] Conventionally, various methods for joining materials, particularly metal materials, have been considered. Among the joining methods, there is a method in which an insert material is placed between members to be joined and the members are joined together.
[0003] For example, Patent Document 1 discloses a method for joining aluminum alloy members using one or more metal or alloy powders selected from silicon, magnesium, zinc, and aluminum as an insert material (brazing material). Patent Document 1 also discloses that joining must be performed in an inert gas atmosphere or in a vacuum in order to avoid or suppress oxidation of the joint during joining.
[0004] Patent Document 2 discloses a brazing sheet (sheet for soldering) for joining aluminum alloy members in an inert gas atmosphere or in a vacuum. Patent Document 2 also discloses that the brazing sheet contains magnesium, which makes it possible to avoid or suppress the oxide film on the brazing sheet surface from interfering with joining.
[0005] Patent Document 3 discloses that when joining aluminum alloy components using an insert material (brazing material), reoxidation of the joining surface is avoided or suppressed by switching from vacuum evacuation to the introduction of an inert gas at a predetermined timing. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-44208 A [Patent Document 2] JP 2018-35386 A [Patent Document 3] JP 2019-155453 A Summary of the Invention [Problem to be solved by the invention]
[0007] In any of the joining methods of Patent Documents 1 to 3, in order to obtain a practically sufficient joining strength when joining metal materials, it was necessary to supply an inert gas throughout the entire joining process or throughout most of the joining process. Therefore, a large amount of inert gas was used during joining, even though the inert gas is expensive. For this reason, the present inventors have found a problem that a method for joining metal materials is required that can obtain a practically sufficient joining strength while reducing the amount of inert gas used as much as possible.
[0008] The present disclosure has been made to solve the above problems. That is, an object of the present disclosure is to provide a method for joining materials that can obtain a practically sufficient joining strength while reducing the amount of inert gas used as much as possible. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to achieve the above object and have completed the bonding method of the present disclosure. The bonding method of the present disclosure includes the following aspects. <1> A method for joining a first member and a second member, comprising the steps of: disposing an insert between the first member and the second member; and While supplying an inert gas, a load is applied to the insert material through at least one of the first member and the second member, the first member, the insert material, and the second member are heated, and the first member and the second member are joined by forming a liquid phase of the insert material; Including, The insert material has a lower melting point than the first member and the second member, and After the insert material forms a liquid phase, the supply amount of the inert gas is reduced. Joining method. <2> The joining method described in <1>, wherein the insert material is composed of a metal or alloy that undergoes a eutectic reaction with the first member and the second member, and the amount of the inert gas supplied is reduced after the insert material forms a liquid phase by the eutectic reaction. <3> The joining method described in <1> or <2>, in which the formation of a liquid phase in the insert material is detected by a change in a reaction force of a load applied to the insert material or a change in a thickness of the insert material. <4> The joining method according to any one of <1> to <3>, wherein at least one of the first member and the second member is made of an aluminum alloy. <5> The joining method described in <4>, wherein the insert material is made of metallic zinc or a zinc alloy. <6> The joining method according to <5>, wherein a formate coating is formed in advance on one or both sides of the insert material. Effect of the Invention
[0010] According to the present disclosure, a method for joining metal materials can be provided in which an inert gas is supplied until the insert material forms a liquid phase, and then the amount of inert gas supplied is reduced, thereby reducing the amount of inert gas used as much as possible while obtaining a joining strength sufficient for practical use. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of the bonding method of the present disclosure. [Diagram 2] FIG. 2 shows the changes over time in bonding pressure and bonding temperature during bonding of the samples of the example and comparative examples 1 and 2. [Diagram 3] FIG. 3 is a graph showing the bonding strength of the samples of Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the bonding method of the present disclosure will be described in detail. Note that the bonding method of the present disclosure is not limited to the embodiments described below.
[0013] Without being bound by theory, the reason why the diffusion bonding of the present disclosure can obtain a practically sufficient bonding strength while reducing the amount of inert gas used as much as possible will be described.
[0014] When the joining surfaces of the first and second members and the insert material are oxidized by oxygen in the joining atmosphere, the wettability of the molten liquid of the insert material is deteriorated by the high melting point oxide film. Then, a part of the molten liquid of the insert material is discharged to the outside of the joint without interdiffusing with the joining surfaces of the first and second members, and the oxide film remains in the joint. When a load is applied to the joint of the joint thus obtained, brittle fracture occurs in the oxide film. Therefore, the joining strength decreases. Therefore, an inert gas is supplied to the joining surfaces of the first and second members and the insert material until the insert material melts and forms a liquid phase. Then, after the insert material forms a liquid phase, the joining surfaces are covered with the liquid phase, so that the oxygen in the joining atmosphere is less likely to come into contact with the joining surfaces. Therefore, after the insert material forms a liquid phase, the supply amount of the inert gas can be reduced.
[0015] The constituent elements of the joining method of the present disclosure, which has been completed based on the findings and the like described thus far, will now be described.
[0016] 《Joining method》 The bonding method of the present disclosure includes an insert material placement step and a bonding step. The bonding method of the present disclosure may also include a formate coating step as an option. Each step will be described below with reference to the drawings. Figure 1 is a cross-sectional schematic diagram showing one embodiment of the bonding method of the present disclosure.
[0017] <Insert material placement process> 1, an insert member 20 is placed between a first member 11 and a second member 12. The first member 11 and the second member 12 are members to be joined.
[0018] The combination of the first member 11 and the second member 12 with the insert material 20 is not particularly limited as long as the insert material 20 has a lower melting point than the first member 11 and the second member 12, and the first member 11 and the second member 12 can be joined using the insert material 20. The first member 11 and the second member 12 may be made of the same material or different materials.
[0019] Typically, the first member 11 and the second member 12 are made of a metallic material, and the insert material 20 is made of a metallic material that can be alloyed with the first member 11 and the second member. Unless otherwise specified, in this specification, "metallic material" means a metal or an alloy. "Metal" means an unalloyed simple metal, and "alloy" means a composition containing two or more elements that are alloyed with each other. "Consists of" means that a material other than the material in question may be contained, and the content of the material in question may be, for example, 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more by mass.
[0020] The joining method of the present disclosure is particularly useful when the first member 11, the second member 12, and the insert material 20 are made of metal materials that are easily oxidized and whose oxide films are likely to adversely affect joining. Examples of such metal materials include aluminum metal and aluminum alloys.
[0021] The purity of the metallic aluminum may be 90% or more, 95% or more, 97% or more, 98% or more, or 99% or more, or may be 100% by mass. For example, metallic aluminum with a purity of 90% or more can be said to contain 90% or more of aluminum, with the remainder being unavoidable impurities. The same applies when the purity is 95% or more, 97% or more, 98% or more, or 99% or more. In this specification, "unavoidable impurities" refers to impurities contained in raw materials or impurities mixed in during the manufacturing process, which cannot be avoided, or which would lead to a significant increase in manufacturing costs if avoided. Impurities mixed in during the manufacturing process include substances that are contained within a range that does not affect the bonding strength, etc., due to manufacturing reasons.
[0022] There is no particular limitation on the type of aluminum alloy as long as there is no particular difficulty in joining. In the joining method of the present disclosure, the insert material 20 is preferably made of an alloy that undergoes a eutectic reaction with the first member 11 and the second member 12. From this viewpoint, the first member 11 and the second member 12 may more typically be made of an aluminum alloy containing silicon. Such an aluminum alloy is easily oxidized during joining, and is also preferable from the viewpoint of the usefulness of the oxidation suppression effect of the joining method of the present disclosure. Examples of such aluminum alloys include aluminum alloys for wrought materials and aluminum alloys for casting, which contain silicon. Unless otherwise specified, in this specification, aluminum alloys for wrought materials include aluminum alloys for forging, and aluminum alloys for casting include aluminum alloys for die casting.
[0023] In the wrought aluminum alloy and the cast aluminum alloy containing silicon, the content of silicon may be, for example, 0.1% or more, 0.5% or more, 0.7% or more, 1.0% or more, 1.5% or more, 2.0% or more, 4.0% or more, 6.0% or more, or 8.0% or more by mass, and may be 24.0% or less, 22.0% or less, 20.0% or less, 18.0% or less, 16.0% or less, 14.0% or less, 12.0% or less, or 10.0% or less. In order to improve age hardenability, corrosion resistance, heat resistance, and / or wear resistance, etc., both the wrought aluminum alloy and the cast aluminum alloy may contain, in addition to silicon, for example, copper, magnesium, zinc, iron, manganese, nickel, titanium, lead, tin, chromium, etc., depending on the application. The total content of the elements other than silicon may be, for example, in mass%, 0.05% or more, 0.1% or more, 0.5% or more, 1.0% or more, 3.0% or more, or 5.0% or more, and 15.0% or less, 13.0% or less, 10.0% or less, or 7.0% or less, with the remainder being aluminum and unavoidable impurities.
[0024] Examples of the aluminum alloy for wrought materials include alloys containing, by mass%, 0.01-5.0% copper, 0.1-1.5% silicon, 0.01-3.0% magnesium, 0-2.0% zinc, iron, manganese, nickel, titanium, lead, tin, and chromium in total, with the remainder being aluminum and unavoidable impurities. In particular, the aluminum alloy for wrought materials may be, for example, the 1000 series, 2000 series, 3000 series, 4000 series, 6000 series, or 7000 series of the Japanese Industrial Standards, and in particular the 4000 series, 6000 series, or 7000 series.
[0025] Examples of the aluminum alloy for casting include alloys containing, by mass%, 0.10-5.0% copper, 4.0-24.0% silicon, 0.1-2.0% magnesium, 0-5.0% zinc, iron, manganese, nickel, titanium, lead, tin, and chromium in total, with the balance being aluminum and unavoidable impurities. In particular, the aluminum alloy for casting may be, for example, AC2A, AC2B, AC2C, AC3A, AC4B, AC4C, AC4CH, AC4D, AC8A, AC8B, AC8C, AC9A, or AC9B, etc., according to the Japanese Industrial Standards.
[0026] In particular, AC2C may contain, for example, by mass%, 0.5-1.1% copper, 6.5-7.5% silicon, 0.2-0.4% magnesium, 0-0.1% zinc, 0-0.1% manganese, 0-0.1% nickel, and 0-0.1% tin, with the remainder being aluminum and unavoidable impurities. In this specification, unless otherwise specified, 0% means that the component may not be contained.
[0027] The aluminum alloy for casting may be an alloy for die casting, for example, an alloy containing, by mass%, 0.10-5.0% copper, 5.0-20.0% silicon, 0-2.0% magnesium, 0-5.0% zinc, iron, manganese, nickel, titanium, lead, tin, and chromium in total, with the balance being aluminum and unavoidable impurities. In particular, the aluminum alloy for die casting may be, for example, ADC3, ADC10, ADC10Z, ADC12, ADC12Z, or ADC14, etc., of the Japanese Industrial Standards, and particularly, ADC10, ADC12, and ADC14, etc.
[0028] In particular, ADC12 may contain, for example, by mass%, 1.5 to 3.5% copper, 9.6 to 12.0% silicon, 0 to 0.3% magnesium, 0 to 0.3% zinc, 0 to 0.5% magnesium, 0 to 0.5% nickel, and 0 to 0.3% tin, with the remainder being aluminum and unavoidable impurities.
[0029] As described above, the insert material 20 is not particularly limited as long as it is a material having a lower melting point than the first member 11 and the second member 12. As the insert material 20, a well-known material that can be used in brazing and liquid phase diffusion bonding can be used. Such an insert material 20 is preferably composed of a metal or alloy that undergoes a eutectic reaction with the first member 11 and the second member 12. This generally allows the insert material 20 to have a lower melting point. As a result, at the time of bonding, the bonding portion of the first member 11 and the second member 12 is surrounded by the liquid phase of the insert material 20 at a lower temperature, improving the effect of suppressing oxidation of the bonding portion.
[0030] When the first member 11 and the second member 12 are made of metallic aluminum or an aluminum alloy, the insert material 20 as described above may be made of metallic zinc or a zinc alloy, for example.
[0031] When the insert material 20 is made of metallic zinc, the purity of the metallic zinc may be, in mass%, 90% or more, 95% or more, 97% or more, 98% or more, or 99% or more, or may be 100%. For example, metallic zinc with a purity of 90% or more can be said to contain 90% or more of zinc, with the remainder being unavoidable impurities. The same applies when the purity is 95% or more, 97% or more, 98% or more, or 99% or more.
[0032] The insert material 20 may be made of a zinc alloy. The zinc alloy means a composition containing, in addition to zinc, an element that alloys with zinc. The content ratio of such alloying elements may be, in mass%, 0.1% or more, 0.5% or more, 1% or more, or 3% or more, and may be 15% or less, 10% or less, 7% or less, or 5% or less. When a plurality of alloying elements are contained, the total content ratio is used. Examples of such alloying elements include copper, aluminum, titanium, lead, tin, cadmium, and iron. It can be said that such a zinc alloy contains, in mass%, 0.1 to 15% of alloying elements, with the balance being zinc and unavoidable impurities.
[0033] The thickness of the insert material 20 may be appropriately determined in consideration of the joining conditions, etc., so that substances derived from the insert material 20 do not remain in the joint after joining and adversely affect the joining strength. The thickness of the insert material 20 may be 0.2 mm or more, 0.4 mm or more, or 0.6 mm, or may be 1.6 mm or less, 1.4 mm or less, 1.2 mm or less, 1.0 mm or less, or 0.8 mm or less.
[0034] <Joining process> As shown in FIG. 1, from a state in which the insert material 20 is disposed between the first member 11 and the second member 12, a load is applied to the insert material 20 through at least one of the first member 11 and the second member 12. At that time, the first member 11, the second member 12, and the insert material 20 are heated to form a liquid phase of the insert material 20, thereby bonding the first member 11 and the second member 12. At that time, an inert gas is supplied to the place where the insert material 20 is disposed and its vicinity until the insert material 20 forms a liquid phase. Then, after the insert material 20 forms a liquid phase, the supply amount of the inert gas is reduced. This makes it possible to reduce the supply amount of the inert gas required for bonding the first member 11 and the second member 12 while suppressing oxidation of the bonding portion. The load is applied in a direction that compresses the thickness of the insert material 20, which is the same as the direction in which the insert material 20 is sandwiched between the first member 11 and the second member 12.
[0035] As described above, in the joining method of the present disclosure, the inert gas is supplied until the insert material 20 forms a liquid phase, and the supply amount of the inert gas is reduced after the insert material 20 forms a liquid phase. When the insert material 20 is made of a metal or alloy that undergoes a eutectic reaction with the first member 11 and the second member 12, the supply amount of the inert gas can be reduced after the insert material 20 forms a liquid phase through the eutectic reaction.
[0036] The supply amount of the inert gas may be appropriately determined in consideration of the ease of oxidation of the first member 11 and the second member 12, the joining temperature, the type of inert gas, and the like, so as to suppress oxidation of the joining portion of the first member 11 and the second member 12 during joining, particularly until the insert material 20 forms a liquid phase. The supply amount of the inert gas may be, for example, 0.001 to 1.000 m under standard conditions until the insert material 20 forms a liquid phase. 3 / min. After the insert material 20 forms a liquid phase, the supply amount of the inert gas may be, for example, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less, or may be 0%, based on the amount before the insert material 20 forms a liquid phase. "After the insert material 20 forms a liquid phase, the supply amount of the inert gas is set to 0% based on the amount before the insert material 20 forms a liquid phase" means that the supply of the inert gas is completely cut off.
[0037] A well-known device can be used for the bonding. For example, the first member 11, the second member 12, and the insert material 20 are stored in a chamber, and the first member 11 and the second member 12 are bonded to each other. Typically, a vacuum pump and an inert gas supply source are connected to the chamber, and the chamber is depressurized by the vacuum pump, and then the inert gas is supplied. When the inert gas is supplied, the operation of the vacuum pump is typically stopped, and the piping connected to the vacuum pump is opened.
[0038] The type of inert gas may be appropriately determined in consideration of the ease of oxidation of the first member 11 and the second member 12, the bonding temperature, the supply amount of the inert gas, and the like, so as to suppress oxidation of the bonding portion of the first member 11 and the second member 12. Typical examples of the inert gas include rare gases such as helium gas, neon gas, argon gas, and krypton gas, nitrogen gas, and carbon dioxide gas. A mixed gas of these may be used. The inert gas may also be a mixed gas obtained by adding a reducing gas to the above-mentioned gases. The reducing gas is typically hydrogen gas.
[0039] The method of detecting the formation of the liquid phase of the insert material 20 is not particularly limited as long as it can be reliably detected, and may be, for example, visual detection or detection using an imaging device. Alternatively, for example, the following method may be used for detection, but is not limited thereto.
[0040] As described above, during joining, a load is applied in a direction to compress the thickness of the insert material 20 through at least one of the first member 11 and the second member 12. For this purpose, for example, a hydraulic cylinder or the like is connected to at least one of the first member 11 and the second member 12 to apply a load to the insert material 20. When a load is applied to the insert material 20, the first member 11 and the second member 12 receive a reaction force of the same magnitude as the load. When the insert material 20 melts and forms a liquid phase, the reaction force decreases. The liquid phase formation of the insert material may be detected by detecting a change (decrease) in this reaction force. Examples of a method for measuring the reaction force include a method in which a load cell or the like is placed between the first member 11 and / or the second member 12 and a hydraulic cylinder.
[0041] Alternatively, when at least a part of the insert material 20 melts and forms a liquid phase, at least a part of the molten insert material 20 is discharged from the space sandwiched between the first member 11 and the second member 12. As a result, the thickness of the insert material 20 changes. The formation of the liquid phase of the insert material may be detected by detecting this change in thickness. As a method for measuring the change in thickness of the insert material 20, for example, a method for measuring the stroke of a hydraulic cylinder can be mentioned.
[0042] The joining temperature may be appropriately determined depending on the type of the first member 11, the second member 12, and the insert material 20. Typically, the joining temperature is equal to or higher than the melting point of the insert material 20, equal to or lower than the melting point of the first member 11 and the second member 12, and preferably equal to or lower than the solution temperature of the joint. When the first member 11 and the second member 12 are made of an aluminum alloy, particularly an aluminum alloy for casting, and the insert material is made of metal zinc or a zinc alloy, the joining temperature may be equal to or higher than 380°C, which is the eutectic temperature of aluminum and zinc, and equal to or lower than the solution temperature of the joint. Specifically, the joining temperature may be, for example, 380°C or higher, 400°C or higher, or 450°C or higher, and may be 660°C or lower, 650°C or lower, 600°C or lower, 550°C or lower, or 500°C or lower.
[0043] The load applied to the insert material can be controlled by the joining pressure. The joining pressure may be appropriately determined so as to be equal to or higher than the pressure at which the insert material 20 does not shift position when the insert material 20 is sandwiched between the first member 11 and the second member 12, and equal to or lower than the pressure at which the joining portion does not deform significantly. The joining pressure may typically be 1 MPa or more, 2 MPa or more, 3 MPa or more, or 4 MPa or more, and may be 25 MPa or less, 20 MPa or less, 15 MPa or less, 10 MPa or less, or 5 MPa or less.
[0044] The bonding time may be appropriately determined so that the insert material 20 is discharged to the outer periphery of the bonded portion by forming a liquid phase with the first member 11 and the second member 12 through a eutectic reaction, or the insert material 20 reaches its melting point and melts, and does not remain in the bonded portion. In addition, when the first member 11 and the second member 12 are made of an alloy and at least a part of the alloy element is solid-solutioned, the bonding time may be appropriately determined in consideration of the time for solution (solid-solution). The bonding time may be, for example, 10 minutes or more, 30 minutes or more, 60 minutes or more, 90 minutes or more, 120 minutes or more, or 150 minutes or more, and may be 300 minutes or less, 270 minutes or less, 240 minutes or less, 210 minutes or less, or 180 minutes or less.
[0045] <Formate Coating Process> When the first member 11 and the second member 12 are made of metal aluminum or an aluminum alloy, and the insert material 20 is made of metal zinc or a zinc alloy, a formate coating may be formed in advance on one or both sides of the insert material. The formate coating can remove the oxide film on the joining surface, and can also prevent or suppress reoxidation of the joining surface. As a result, the joining strength can be improved. Without being bound by theory, it is believed that this is because the formate coating is thermally decomposed during joining to remove the oxide film on the joining surfaces of the first member 11 and the second member 12.
[0046] An example of a method for forming the formate coating is to immerse a foil or plate material for the insert member 20 in boiling formic acid for 1 to 5 minutes, and then rinse with water.
[0047] In addition to what has been described so far, the joining method of the present disclosure can be modified in various ways within the scope of the claims. EXAMPLES
[0048] The bonding method of the present disclosure will be described in more detail below with reference to examples and comparative examples. Note that the bonding method of the present disclosure is not limited to the conditions used in the following examples.
[0049] <Preparation of joint specimen> The joint specimens were prepared as follows.
[0050] Example As shown in FIG. 1, an insert material 20 was placed between a first member 11 and a second member 12, and the first member 11 and the second member 12 were joined to obtain a joint sample of the example.
[0051] Both the first member 11 and the second member 12 were made of a Japanese Industrial Standard AC2C-F aluminum alloy for casting, which contained, by mass%, 0.5 to 1.1% copper, 6.5 to 7.5% silicon, 0.2 to 0.4% magnesium, less than 0.1% zinc, less than 0.1% manganese, less than 0.1% nickel, and less than 0.1% tin, with the remainder being aluminum and unavoidable impurities. The joint surfaces (surfaces in contact with the insert material 20) of the first member 11 and the second member 12 were roughened using #1200 abrasive paper before joining.
[0052] The insert material 20 was a zinc alloy foil having a thickness of 0.4 mm. The zinc alloy foil had a composition containing, by mass%, 0.30% copper, 0.002% aluminum, 0.02% titanium, less than 0.02% lead, less than 0.01% cadmium, and less than 0.01% iron, with the remainder being zinc and unavoidable impurities.
[0053] A formate coating was formed in advance on both sides of the insert material 20. The formate coating was formed by immersing the zinc alloy foil in boiling formic acid for 2 minutes.
[0054] The liquid phase diffusion bonding conditions were as follows. Junction temperature: 500℃ Bonding pressure: 5MPa Bonding time: 180 minutes Supply gas: Nitrogen Supply amount: 0.005m 3 / min
[0055] Then, when the insert material 20 formed a liquid phase, the supply of nitrogen gas was stopped. The formation of the liquid phase was detected by the reaction force of the load (joining pressure) applied to the insert material. Figure 2 shows the change over time in the joining pressure and the joining temperature during joining. The joining pressure is the reaction force (pressure) measured by a load cell attached to a hydraulic cylinder connected to the first member 11.
[0056] Comparative Example 1 A joint sample of Comparative Example 1 was obtained in the same manner as in Example, except that nitrogen gas was continuously supplied from the start of joining to the end of joining.
[0057] Comparative Example 2 A joint sample of Comparative Example 2 was obtained in the same manner as in Example, except that joining was carried out in the air without supplying nitrogen gas.
[0058] "evaluation" A tensile test was performed on each of the bonded joint samples to measure the bond strength (fracture strength). The tensile direction was approximately opposite to the compression direction of the insert material 20. The tensile speed was 10 mm / min. In addition, the fracture surface of each of the bonded joint samples after the tensile test was observed using a scanning electron microscope, and surface analysis of oxygen was performed using EDX.
[0059] The measurement results of the bonding strength are shown in FIG. 3. From FIG. 3, it was confirmed that the bonding strength of the sample of the embodiment is lower than that of the sample of Comparative Example 1 in which nitrogen gas was continuously supplied from the start of bonding to the end of bonding, but the sample of the embodiment has a bonding strength sufficient for practical use. In contrast, it was confirmed that the bonding strength of the sample of Comparative Example 2, which was bonded in the air without supplying nitrogen gas, was significantly lower. From these facts, it was confirmed that a practically sufficient bonding strength can be obtained even if the supply of nitrogen gas is stopped at the time when the liquid phase of the insert material is formed, as in the embodiment. In addition, as a result of the surface analysis of the fracture surface after the tensile test, it was confirmed that the amount of oxygen in the sample of the embodiment is smaller than that of the sample of Comparative Example 2, and that oxidation of the joint can be suppressed during the preparation of the sample of the embodiment.
[0060] From the above results, the effectiveness of the joining method of the present disclosure was confirmed. [Explanation of symbols]
[0061] 11 First member 12 Second member 20 Insert material
Claims
1. A method for joining a first member and a second member, comprising the steps of: disposing an insert between the first member and the second member; and While supplying an inert gas, a load is applied to the insert material through at least one of the first member and the second member, the first member, the insert material, and the second member are heated, and the first member and the second member are joined by forming a liquid phase of the insert material; Including, The insert material has a lower melting point than the first member and the second member, After the insert material forms a liquid phase, the supply amount of the inert gas is reduced; and The liquid phase formation of the insert material is detected based on a change in a reaction force of a load applied to the insert material or a change in a thickness of the insert material. Joining method.
2. The joining method according to claim 1, wherein the insert material is composed of a metal or alloy that undergoes a eutectic reaction with the first member and the second member, and the amount of the inert gas supplied is reduced after the insert material forms a liquid phase by the eutectic reaction.
3. The joining method according to claim 1 or 2, wherein at least one of the first member and the second member is made of an aluminum alloy.
4. The joining method according to claim 3 , wherein the insert material is made of metallic zinc or a zinc alloy.
5. The joining method according to claim 4 , wherein a formate coating is formed in advance on one or both sides of the insert material.
Citation Information
Patent Citations
Method and equipment for joining wide flange beam
JP1996206852A
Method and device for liquid phase diffusion welding
JP2007098402A
Brazing method of aluminum alloy material and method of manufacturing brazed structure
JP2015044208A
Joint method
JP2015199076A
Aluminum alloy brazing sheet
JP2018035386A